Oxalate as a potent promoter of kidney stone formation - Chen, Tao; Qian, Biao; Zou, Junrong; Luo, Peiyue; Zou, Jun; Li, Wei; Chen, Qi; Zheng, Liying (Frontiers in Medicine, 2023)
Kidney stones are among the most prevalent urological diseases, with a high incidence and recurrence rate. The treatment of kidney stones has been greatly improved by the development of various minimally invasive techniques. Presently, the treatment of stones has been relatively mature. However, most of the current treatment methods are limited to the stones themselves and cannot effectively reduce the incidence and recurrence of stones. Therefore, preventing the occurrence and development of the disease, as well as its recurrence after treatment, has become an urgent issue to be solved. The etiology and pathogenesis of stone formation are the key factors in resolving this issue. More than 80% of kidney stones are calcium oxalate stones. Several studies have studied the formation mechanism of stones from the metabolism of urinary calcium, but there are few studies on oxalate, which plays an equally important role in stone formation. Because both oxalate and calcium play an equally important role in calcium oxalate stones, the metabolism and excretion disorders of oxalate play a crucial role in the occurrence of calcium oxalate stones. Therefore, starting from the relationship between renal calculi and oxalate metabolism, this paper reviews the occurrence of renal calculi, oxalate absorption, metabolism, and excretion mechanisms, focusing on the key role of SLC26A6 in oxalate excretion and the regulatory mechanism of SLC26A6 in oxalate transport. This review provides some new clues for the mechanism of kidney stones from the perspective of oxalate, to improve the understanding of the role of oxalate in the formation of kidney stones and to provide some suggestions for reducing the incidence and recurrence rate of kidney stones.